Knowledge gaps among smallholder farmers hinder adoption of conservation biological control. Issue 3 (3rd March 2020) - Mkenda, Prisila A.; Ndakidemi, Patrick A.; Stevenson, Philip C.; Arnold, Sarah E.J.; Darbyshire, Iain; Belmain, Steven R.; Priebe, Jan; Johnson, Anne C.; Tumbo, Julie; Gurr, Geoff M.
ABSTRACT: Conservation biological control uses habitat management to enhance the survival and impact of arthropod natural enemies for pest control. Its advantages are that it relies on native or established invertebrate populations that are adapted to local agricultural ecosystems and conditions. We surveyed 300 farmers in three agro-ecological zones of Kilimanjaro Region, Tanzania to assess farmers' knowledge of natural enemies, insect pests and pesticide use and ways of accessing agricultural information to identify hurdles to the adoption of conservation biological control measures. Data were collected through face to face interviews using questionnaires and pictures and by using a novel voice-response mobile phone survey. The farmers surveyed regarded almost all insects as pests, with data analyses revealing that 98.7% of farmers were completely unaware of natural enemies. After completing a short training course, however, awareness was transformed, with 80% of farmers recognising beneficial insects and expressing an intention to change farming practices to enhance their survival within the crop. Access to information about synthetic pesticide alternatives was a limiting factor to uptake of biological control measures with 8.7% of farmers reporting no access to agricultural information, while others were mostly dependent on agricultural officers. These findings identified a severe lack of knowledge among smallholder farmers about beneficial insects which will impact adoption of conservation biological control. We recommend improved access to information and knowledge among the technical officers and the smallholder farmers with direct training on agro-ecological intensification for wider adoption of conservation biological control.